Azerbaijan : Leveraging Postal Network for Financial and Social Inclusion - Prigozhina, Angela (World Bank, Washington, DC, 2016)
This paper provides a brief overview of the postal network reform in Azerbaijan and transformation of Azerpost, Azerbaijan’s state postal operator, into an efficient platform for basic financial services delivery throughout the country. This complex reform, supported by the World Bank loan for Financial Services Development Project and the grants from the Swiss Office of International Cooperation (SECO), was launched in 2006 and helped the government of Azerbaijan to improve financial services delivery and inclusion in the country in parallel with modernizing and digitalizing Azerpost, expanding its financial services delivery capacity, enhancing its financial viability and maximizing the public value of Azerpost extensive branch network of 1,600 offices. In the period of 2007-1H2015, Azerpost total revenues, largely from financial services (as universal postal services remain loss-making) tripled, while volume of financial services’ sales increased four times. In 2015, Azerpost reached financial breakeven without state subsidy, and productivity of its staff increased 3 times. In 2009, Azerpost corporatized and became LLC, while in 2010, based on the new postal legislation, it was licensed as a non-bank financial institution subject to prudential supervision of the central bank.